A Study on The Implementation of Land Use Policies in River Boundaries in Indonesia - Novilyansa, Elza; Wulandari, Christine; Bakri, Samsul (Universitas Sang Bumi Ruwa Jurai, 2024)
Riverbanks play a crucial role in maintaining water quality, preventing floods, and supporting the daily activities of the community. However, there is often a change in the function of riverbank land for construction or settlements, which can result in negative impacts such as flooding, soil erosion, and material and non-material losses for the surrounding community. Law No. 32 of 2009 on Environmental Protection and Management (PPLH) regulates that riverbank boundaries must be protected and managed properly. Prohibitions on construction that endanger the river ecosystem or damage the river flow are also included in these provisions. The Regulation of the Minister of Public Works and Public Housing Number 28/PRT/M/2015 further regulates the riverbank and lake boundaries. The division of authority for water resource management from the central, provincial, to district/city level has also been regulated in Law Number 23 of 2014 concerning Regional Government. To understand the compliance of land use with laws and technical regulations along the river, a study on the existing condition of land use in various regions is needed. This study aims to evaluate the extent to which land use complies with applicable legal rules. Considering the important role of riverbanks and the steps that support compliance with the law need to be strengthened and consistently applied